(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
In scientific articles specified indicators professional levels of future physical training teachers. Theoretical analysis and generalization of teaching experience made it possible to figure out that the problem of professional training future teachers of physical education is considered in the context of updating of educational process in high school, forming needs professional self-development specialist in the field of sports and continuous improvement of pedagogical skills. The purpose of the work: is to consider the structure of professional self-development of future physical education teachers as a set of three interrelated components: motivational-emotional, content-operational and reflective. The set of selected arguments allows us to talk about the positive impact of the selected criterion of educational and methodological (pedagogical) provision on the humanization of higher physical education and pedagogical education, since increasing the level of self-organization in the preparation and implementation of personally significant pedagogical activities expands the free search and mastering of new knowledge, skills and abilities, attachment to the values of education, trustful communication, equal relations, and, therefore, reveals the potential opportunities of students in the process of self-development, stimulating their professional self-development. Self-development of the future physical education teacher is considered as a relatively independent activity of the student to make changes to his own educational trajectory, improve professional qualities, expand knowledge potential, increase the level of pedagogical and sports qualifications, aimed at mastering modern pedagogical ideas and technologies, which ensures the professional growth of the teacher, improving the quality of education and educating students. Theoretical analysis and generalization of pedagogical experience made it possible to find out that the problem of professional training of future physical education teachers is considered in the context of updating the educational process in higher education, forming the need for professional self-development of a specialist in the field of sports and continuous improvement of pedagogical skills for students, teachers and researchers working in sphere of physical education.